Development of White Matter Hyperintensity Is Preceded by Reduced Cerebrovascular Reactivity. Issue 2 (August 2016) - Sam, Kevin; Crawley, Adrian P.; Conklin, John; Poublanc, Julien; Sobczyk, Olivia; Mandell, Daniel M.; Venkatraghavan, Lakshmikumar; Duffin, James; Fisher, Joseph A.; Black, Sandra E.; Mikulis, David J.
Abstract : Objective: White matter hyperintensities (WMH) observed on neuroimaging of elderly individuals are associated with cognitive decline and disability. However, the pathogenesis of WMH remains poorly understood. We observed that regions of reduced cerebrovascular reactivity (CVR) in the white matter of young individuals correspond to the regions most susceptible to WMH in the elderly. This finding prompted us to consider that reduced CVR may play a role in the pathogenesis of WMH. We hypothesized that reduced CVR precedes development of WMH. Methods: We examined 45 subjects (age range = 50–91 years; 25 males) with moderate–severe WMH, and measured their baseline CVR using the blood oxygen level–dependent magnetic resonance imaging signal response to a standardized step change in the end‐tidal partial pressure of carbon dioxide. Diffusion tensor imaging and transverse relaxation time (T2) relaxometry were performed at baseline and 1‐year follow‐up, with automated coregistration between time points. Baseline fractional anisotropy (FA), mean diffusivity (MD), T2, and CVR were measured in areas that progressed from normal‐appearing white matter (NAWM) to WMH over the 1‐year period. Results: CVR and FA values in baseline NAWM that progressed to WMH were lower by mean (standard deviation) = 26.5% (23.2%) and 11.0% (7.2%), respectively, compared to the contralateral homologous NAWM that did not progress ( p < 0.001). T2 and MD were higher by 8.7% (7.9%) and 17.0% (8.5%), respectively, compared to the contralateral homologous NAWM ( p < 0.001). Interpretation: Areas of reduced CVR precede the progression from NAWM to WMH, suggesting that hemodynamic impairment may contribute to the pathogenesis and progression of age‐related white matter disease. Ann Neurol 2016;80:277–285